The silent girl - Gerritsen, Tess (Gerritsen, Tess. Rizzoli & Isles novel., 2011)
Boston homicide detective Jane Rizzoli is already at the crime scene when medical examiner Maura Isles arrives on the Chinatown rooftop. Rizzoli's gut says they're on the trail of a twisted predator and when a monkey hair is found on the body, other clues point Rizzoli and Isles in the direction of the fable of the Monkey King.